Sorption of sulfadiazine in urban soil: experimentation and modeling - Silva Júnior, Emidio Dias (2019)
The evaluation of the interaction of pollutants in the vadose zone is fundamental for determining the degree of vulnerability of groundwater when transporting contaminants in the soil. The present work presents the interaction of an antibiotic of the type Sulfaziadina in urban soil in the city of Recife. The kinetics and sorption isotherm of Sulfadiazine (SDZ) were determined in a sandy-loam soil of the urban area of the city of Recife. Sorption kinetics and sorption isotherms were performed in for layers of an urban soil profile. Sulfadiazine concentration was determined by high performance liquid chromatography (HPLC). The kinetics studies showed that the sorption was rapid in the first ten hours of the contact period between the soil and the SDZ solution. The equilibrium was reached with 24 hours if interaction in 04 layers. For this soil, SDZ sorption kinetics were reasonably described by a first order model.The second order kinect model presented the best adjustments of sorption kinetics at all depths with R2 values between 0.94 and 0.98. The model that best fit the representation of sorption isotherms was the Linear model. The low KD values (1.3 to 1.9 L.kg-1) indicate high mobility and high risk of groundwater contamination by this compound.